An efficient route to 3-trifluoromethylpyrazole via cyclization/1, 5-H shift and its applications in the synthesis of bioactive compounds. Issue 43 (28th October 2015) - Wang, Yongdong; Han, Jing; Chen, Jie; Cao, Weiguo
Abstract: A methodology for regioselective synthesis of 3-trifluoromethylpyrazole from the reaction of trifluoromethyl alkenone and tosylhydrazone has been developed. The reaction was proposed to proceed through a tandem cyclization and 1, 5-H shift reaction, which can be applied to the synthesis of bioactive compounds like Celecoxib, Mavacoxib, and SC-560. Graphical abstract: